Experience of implementation of Eurocodes in the design of steel structures in the Republic of Belarus - ﻿A. B. Shuryn; V. V. Nadolski (Vestnik MGSU)
Introduction. The Republic of Belarus is one of the first countries on the territory of the CIS, which introduced European design standards (Eurocodes) on its territory, while preserving the effect of building standards developed on the basis of Soviet SNIP. The republic accumulated considerable experience in the practical application and comparative analysis of these two systems of standards. The relevance of this study is contained in the discovery of the most distinctive features of normative documents, on the basis of which it is possible to determine further directions of scientific research and improvement of domestic norms.Materials and methods. Analysis and generalization of experience.Results. The paper presents the results of generalization of the experience of practical application and comparative analysis of Eurocode and CP in relation to the design of steel structures. The analysis of partial factors, classification of cross sections, welded and bolted joints is given.Conclusions. Methodological approaches to checking limit states and ensuring the reliability of steel structures in CP and Eurocodes are very similar, but there are differences in the values and sets of partial factors. When designing steel structures according to Eurocode, the methods of classification of cross-sections of rolled profiles produced according to GOST or TS need to be adjusted. Eurocode 3 provides more possibilities in the design of welded and bolted joints.